Unifying business objects and system dynamics as a paradigm for developing decision support systems - Gregoriades, Andreas; Karakostas, Bill (My University, 2004)
Due to the market-driven nature of modern organisations, it is important that they can easily adapt to changing business needs. In order to be able to do so, organisations need to employ information systems that exhibit the important characteristic of adaptability. Change, however, is risky because it encompasses unpredictable behaviours. Organisations, in order to minimise this risk, employ decision support systems (DSS) techniques that enable predictions to be made. This paper describes a simulation methodology, based on the combination of business objects and system dynamics that assists organisations in predicting future behaviours. The methodology eliminates the need for duplicate models of enterprise operation and simulation, and introduces a framework that enables the unification of the two in a single model.
Keywords: Business objects; Simulation; System dynamics; Mathematical programming